Pola Sinergitas Tri Pusat Pendidikan dalam Habituasi Sikap Remaja Usia Pendidikan Menengah - Ismail Darimi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The adolescent phase is a developmental phase with great potential, both in terms of affective, cognitive, and psychomotor aspects. Adolescents are usually at the age of 15/17 years, at this age children have a tendency to imitate and are easily influenced by educational tri-centers such as family, school and community. The method used in this study is descriptive analysis method, which is a method that includes recording, parsing, interpreting, analyzing existing data. The type of research that the author uses is library Research. Child development must start early in the family, the main education is both parents at home, the most important method is an example in addition to other methods according to psychological conditions and situations, because other materials should be taught with a strong foundation of faith in conditions of worship, morality and others. Furthermore, youth development when entering school, children must be equipped with an initial understanding of socializing with their friends. In the community environment, children must be monitored or noticed their movements such as choosing good friends and avoiding promiscuity.